Decrease in Fishery Yields in Response to Hydrological Alterations in the Largest Floodplain Lake (Poyang Lake) in China - Li, Mingzheng; Liu, Chang; Liu, Fei; Wang, Jianwei; Liu, Huanzhang (Frontiers in Earth Science, 2022)
Habitat degradation has caused reduction in fishery yields in many freshwater ecosystems, particularly recession of water levels in natural lakes. Poyang Lake, the largest freshwater lake and one of the most exploited regions in China, has exhibited a dramatic variation in the water level for decades, especially after the operation of the Three Gorges Dam. We evaluated the long-term dynamics of fishery yields and the relationship to hydrological variability of Poyang Lake from 1990 to 2016. There was a strong positive effect on the annual maximum water level (Hmax), the minimum water level in April (HMmin4), the maximum water level in August (HMmax8), the average water level in October (HMmean10), and the number of days when the water level was above the wet threshold (Wetdays) on fishery yields. The all-subsets regression model identified the best variable combination subset which contains eight hydrological variables (R2 = 0.9493), and the HMmin4, HMmax8, and HMmean10 variables were the most important variable predictor for fishery yields (contributing to 63.03% of the explained variability). The Mann–Kendall test showed that the time series of the fishery yield of Poyang Lake had significant decreasing trends over the past few decades. Moreover, Wetdays, HMmin4, and HMmean10 also showed significantly decreasing abrupt changes, and the abrupt changes’ time of HMmean10 was the same as that of the fishery yield in 2005. The mean fishery yield and HMmean10 dropped from 42,581 tonnes and 14.15 m during 1990–2005 to 27,464 tonnes and 11.78 m during 2006–2016, respectively. This study is critical for implementing effective strategies for the protection of fish resources and lake ecosystems.